Facilitating Digital Transformation in Construction—A Systematic Review of the Current State of the Art - Olanipekun, Ayokunle O.; Sutrisna, Monty (Frontiers in Built Environment, 2021)
There is increasing implementation of digital technologies in construction. However, the transformation effects encompassing digital technology implementation is yet to be fully comprehended within the context of construction. Therefore, this study was aimed to provide a holistic understanding of digital transformation in construction. The study drew on extant literature by studying 36 journal publications published between 2016 when digital transformation emerged in construction from the Information Systems (IS) field and 2020. This led to the development of an inductive framework using a Grounded Theory Methodology (GTM) to highlight digital transformation in construction as a process where the implementation of digital technologies creates transformation effects which trigger strategic considerations for putting in place the enablers that facilitate transformation effects and for suppressing the barriers to it. Building on the framework, this study described and presented the strategic considerations for facilitating specific enablers and those for suppressing specific barriers as digital transformation guideline in construction. This study demonstrated how the implementation of digital technologies has increased the understanding of and provided the basis for digital transformation in construction.